Keep it real - Dower, Laura (New York : Volo/Hyperion, 2005)
Madison learns through a weblog that her friend Ivy's life is not as perfect as Ivy would have the world believe.
Keywords: Girls -- Juvenile fiction; Friendship -- Juvenile fiction; Blogs -- Juvenile fiction; Schools -- Juvenile fiction; Girls -- Fiction; Friendship -- Fiction; Blogs -- Fiction; Schools -- Fiction; Children's stories